Hsa-miRNA-31 regulates epithelial cell barrier function by inhibiting TNFSF15 expression - Nan, X; Qin, S; Yuan, Z; Li, Y; Zhang, J; Li, C; Tan, X; Yan, Y (Cellular and Molecular Biology, 2016)
Ulcerative colitis (UC) is characterized by epithelial barrier disruption and alterations in immune regulation but with the etiology unknown. MicroRNA-31 is the most consistent differentially expressed miRNA in ulcerative colitis tissue. The aim of this project is to study the important roles of miRNA-31 in regulation of intestinal epithelial barrier function. We found that expression of miRNA-31 is proportional to the proliferation of Caco2-BBE cells and overexpression of miRNA-31 can increase its trans-epithelial resistance (TER) by decreasing the transepithelial permeability. miRNA-31 can directly bind to the 3-UTR of TNFSF15, thereafter negatively regulating its expression in Caco2-BBE cells. BrdU and TUNEL analysis demonstrated that transfection of miRNA-31 stimulates proliferation or apoptosis-resistance. Taken together, these results revealed a novel mechanism underlying the regulation of epithelial barrier function by miRNA-31 during its regulation on proliferation of epithelial cells.